Relationship between lactation length and weaning service interval and subsequent sow productivity traits in an intensive swine production system - Kinejara Espinoza, Ana Laura; Barreras Serrano, Alberto; Soto Ávila, José Guadalupe; Sánchez López, Eduardo; Herrera Haro, José G. (Acta Universitaria, 2016)
Relationship between lactation length (LL), weaning service interval (WSI) and number of piglets born (NPB), piglets born alive (PBA), birth weight (BW) and weaning weight (WW) were investigated. Influence of environmental components and linear and quadratic effects of LL, and WSI on subsequent productivity were analyzed by ANOVA. Only 24.4% of females showed estrus between 5 to 7 days after weaning. In the NP ≤ 2 females group, PBA values were different (p < 0.05) to WSI class. WSI higher than 7 days were observed when LL ≤ 21 days. A one-day increase in LL resulted in a decrease in 0.066 piglets for subsequent PBA. If WSI increases from 7 to 12 days and LL was fixed in 21 days, increase in piglets was of 0.07 for PBA. Besides, for each one-day increase on LL, a 0.235 kg increase may be expected in subsequent WW.
Keywords: Array; Array; Array; Array